Perfusion Index Analysis in Patients Presenting to the Emergency Department Due to Synthetic Cannabinoid Use - Selman Yeniocak (Medicina, 2019)
Background and objectives: The perfusion index (PI) indicates the ratio of pulsatile blood flow in peripheral tissue to non-pulsatile blood flow. This study was performed to examine the blood perfusion status of tissues and organs of patients using synthetic cannabinoids (SCs). Materials and Methods: The records of patients aged 17 or over presenting to the adult emergency department due to SC use between 1 January 2016 and 31 December 2017 were examined in this single-center, retrospective, cross-sectional study. Examined factors included time from consumption of SC to presentation to the emergency department, as well as simultaneously determined systolic and diastolic blood pressures, heart rate (beats per min), Glasgow Coma Score (GCS), and PI values. Patients were divided into two groups, A and B, depending on the amount of time that had elapsed between SC consumption and presentation to the emergency department, and statistical data were compared. Results: The mean PI value in Group A was lower than that in Group B. Therefore, we concluded that peripheral tissue and organ blood perfusion is lower in the first 2 h following SC consumption than after 2 h. Systolic, diastolic, and mean arterial blood pressure and mean GCS values were also statistically significantly lower in Group A than in Group B. Conclusions: A decreased PI value may be an early sign of reduced-perfusion organ damage. PI is a practical and useful parameter in the early diagnosis of impaired organ perfusion and in monitoring tissue hypoxia leading to organ failure.